Keberkesanan Pusat Aktiviti Warga Emas (PAWE) di bawah Dasar Warga Emas Negara (Jurnal Pembangunan Sosial, 2016)
Population aging is a phenomenon that will hit Malaysia in the 21st century. According to the United Nations (UN) in a report issued in 2007, older person in Malaysia are expected to increase from 7 percent to 14 percent in 2030 within 28 years as opposed to the country Sweden, which took 112 year for the same change. Recognizing this, the Government has formulated the National Policy for the Elderly in 1995. Later this policy and plan has been improved on 5 January 2011 as a Dasar Warga Emas Negara (DWEN). Older Person Activity Center (PAWE) is a development program that has been established under DWEN program since 2001. The establishment of PAWE seen as an alternative to address the issues and challenges of older persons in the present and future. A survey was conducted to see effectiveness PAWE to level of wellbeing among 78 elderly people who were present at the following activities PAWE located at Selangor. This study uses interview and convinience sampling technique. Results show that the respondents level of wellbeing is at a high level and prove effectiveness PAWE can help well-being of the older persons in Malaysia. This directly helps the government to improve the programs in PAWE.